The evolution of Green Belt concepts in Hanoi’s regional planning, 1960-2023 - Dinh, Theanh; Hoang, Ngoc Huyen; Nguyen, Quynh Duong; Le, Thuy Trang (International Planning History Society Proceedings, 2024)
This article analyses the evolution of Green Belt concepts in Hanoi from a historical perspective. Through the comparison between international concepts and the practical planning local during 1960 - 2023, this paper aims to answer three main questions related to the Green Belt: First, when was the Green Belt theory introduced to Vietnam? Second, what lessons were there in the process of being introduced into Hanoi? Third, why has the Green Belt theory not been successful in practical planning? This article uses fieldwork methods and comprehensive analysis and divides three different periods: the first period (1960-1998), the second period (1998-2011), and the third period (2011-2023). The planners have found many ways to enhance Greenbelt’s role, from changing perception to changing form toward flexibility, but Greenbelt theory still can not be put into practical planning. This article adopts a comparative historical planning perspective to examine the adaptability of planning applications across diverse contexts, with a specific focus on the paradigm in the UK where this theory originated and has successfully adapted through numerous policy and institutional changes. Hanoi’s green belt had faced various challenges arising from ambiguity in green belt identification; the development of appropriate frameworks tailored to local conditions for managing the green belt as a cohesive entity, and consideration of the overall urban development layout with a long-term perspective.